Risk factors for extrauterine growth restriction in preterm neonates: a prospective analytical cohort study - Roshan, Reashma; Naik, Suhail A.; Shah, Mubashir H. (International Journal of Research in Medical Sciences, 2022)
Background: Objective of the study was to determine the incidence and risk factors for extrauterine growth restriction (EUGR) at discharge in preterm neonates. Methods: This prospective analytical cohort study included 107 preterm neonates between 30-35 weeks of gestational age who were admitted to a tertiary neonatal intensive care unit from January 2016 to December 2016. These preterm neonates were classified into EUGR group (n=93) and non-EUGR group (n=14) based on the body weight at discharge. The risk factors for EUGR were analyzed statistically. Results: The incidence of EUGR at discharge was 87.4% in the cohort. Delay in initiation of parenteral nutrition (p=0.04), longer time to reach full enteral feeds (p=0.03), very low birth weight (p=0.01), small for gestational age (p=0.01), intrauterine growth restriction (p=0.01), necrotizing enterocolitis (p=0.03), late-onset sepsis (p=0.03) and bronchopulmonary dysplasia (p=0.04) were significant risk factors for extra-uterine growth restriction at discharge in preterm neonates. Conclusions: The incidence of EUGR can be decreased by improving perinatal care, minimizing preterm deliveries, early initiation of parenteral nutrition and enteral feeding and reducing immediate postnatal complications.